2022
DOI: 10.3390/machines10020130
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Analysis of an Enhanced Multi-Frequency Inertial Exciter for Industrial Vibrating Machines

Abstract: Multi-frequency vibrators have advantages in bulk materials processing but their design is usually complicated. This article presents the synthesis of design parameters of a two-frequency inertial vibrator according to the specified power characteristics. Based on the developed mathematical model, the parameters of variable periodic force is derived for two angular velocities 157, 314 rad/s and their ratios 0.5 and 2. In the case of the 0.5 ratio, the instant angular velocity of the resulting force vector is 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Considering numerous scientific publications related with inertial exciters, in particular, those [1]- [11] mentioned above, it can be concluded that the problems of implementing the planetarytype exciters for providing the controllable kinematic and dynamic parameters of the vibratory equipment are not thoroughly investigated. Therefore, the present paper continues the authors' previous investigations presented in [12]- [14] and devoted to improving the controllable vibration exciters able to ensure the efficient operation of various vibratory equipment under the changeable loading conditions. The major scientific novelty of the paper consists in substantiating the parameters of the symmetric planetary-type vibration exciter allowing for generating triangular, rectangular, hexagonal, and other paths of oscillations of the single-mass vibratory system.…”
Section: Introductionsupporting
confidence: 66%
“…Considering numerous scientific publications related with inertial exciters, in particular, those [1]- [11] mentioned above, it can be concluded that the problems of implementing the planetarytype exciters for providing the controllable kinematic and dynamic parameters of the vibratory equipment are not thoroughly investigated. Therefore, the present paper continues the authors' previous investigations presented in [12]- [14] and devoted to improving the controllable vibration exciters able to ensure the efficient operation of various vibratory equipment under the changeable loading conditions. The major scientific novelty of the paper consists in substantiating the parameters of the symmetric planetary-type vibration exciter allowing for generating triangular, rectangular, hexagonal, and other paths of oscillations of the single-mass vibratory system.…”
Section: Introductionsupporting
confidence: 66%
“…Similar locomotion principles have been implemented in the improved vibratory compactor, which can slide along a rough surface and is equipped with the crank-type vibration exciter [13]. In [14], the authors proposed the enhanced inertial vibration exciter equipped with two synchronized and coaxially rotating unbalanced masses. The paper [15] is focused on studying the locomotion conditions of the wheeled vibration-driven robot with the double-mass oscillatory system and crank-type exciter.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the existent vibration-driven wheeled robots, in particular those considered in [7] and [8], are equipped with the inertial vibration exciters designed in the form of the unbalanced rotating masses. The possibilities of implementing the controllable multi-regime operational conditions of the vibratory machines with inertial exciters are thoroughly analyzed in [9].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of numerous investigations (e.g., [1]- [9]) has shown that the possibilities of implementing the crank-slider excitation mechanisms in the vibration-driven wheeled robots are not thoroughly investigated, especially under the vibro-impact operational conditions. Therefore, the previous authors' papers were dedicated to studying the dynamic characteristics of the vibroimpact locomotion system with the twin crank-slider excitation mechanism [10], and analyzing the operational conditions of the vibratory compacting machine equipped with the crank-type drive [11].…”
Section: Introductionmentioning
confidence: 99%